Proceso de atención de enfermería en escolar con bronquitis aguda. - Contreras Franco, Litzy Leonela (2022)
Bronchitis is an inflammation of the airways or airways, accompanied by mucus and airway damage. Two types of bronchitis have been identified: acute and chronic. Acute bronchitis is an inflammation of the mucous membranes of the airways. The main objective for which this case study was carried out is to contribute with scientific knowledge of the disease to be treated, and development of nursing procedures for pediatric patients with acute bronchitis. For this reason, an exhaustive evaluation is carried out, through the assessment of the 11 Functional Patterns of Marjorie Gordon, to determine the interventions to follow and obtain a complete care plan, whose objective is to provide interventions that contribute to the improvement in the patient's health status